Arabidopsis ALIX Regulates Stomatal Aperture and Turnover of Abscisic Acid Receptors. Issue 10 (30th July 2019) - García-León, Marta; Cuyas, Laura; El-Moneim, Diaa Abd; Rodriguez, Lesia; Belda-Palazón, Borja; Sanchez-Quant, Eva; Fernández, Yolanda; Roux, Brice; Zamarreño, Ángel María; García-Mina, José María; Nussaume, Laurent; Rodriguez, Pedro L.; et al.
Abstract : ALIX mediates endosomal trafficking and turnover of abscisic acid receptors through the ESCRT/MVB pathway, modulating abscisic acid–mediated inhibition of plant growth and stomatal aperture. Abstract: The plant endosomal trafficking pathway controls the abundance of membrane-associated soluble proteins, as shown for abscisic acid (ABA) receptors of the PYRABACTIN RESISTANCE1/PYR1-LIKE/REGULATORY COMPONENTS OF ABA RECEPTORS (PYR/PYL/RCAR) family. ABA receptor targeting for vacuolar degradation occurs through the late endosome route and depends on FYVE DOMAIN PROTEIN REQUIRED FOR ENDOSOMAL SORTING1 (FYVE1) and VACUOLAR PROTEIN SORTING23A (VPS23A), components of the ENDOSOMAL SORTING COMPLEX REQUIRED FOR TRANSPORT-I (ESCRT-I) complexes. FYVE1 and VPS23A interact with ALG-2 INTERACTING PROTEIN-X (ALIX), an ESCRT-III–associated protein, although the functional relevance of such interactions and their consequences in cargo sorting are unknown. In this study we show that Arabidopsis ( Arabidopsis thaliana ) ALIX directly binds to ABA receptors in late endosomes, promoting their degradation. Impaired ALIX function leads to altered endosomal localization and increased accumulation of ABA receptors. In line with this activity, partial loss-of-function alix-1 mutants display ABA hypersensitivity during growth and stomatal closure, unveiling a role for the ESCRT machinery in the control of water loss through stomata. ABA-hypersensitive responses are suppressed in alix-1 plants impaired in PYR/PYL/RCAR activity, in accordance with ALIX affecting ABA responses primarily by controlling ABA receptor stability. ALIX-1 mutant protein displays reduced interaction with VPS23A and ABA receptors, providing a molecular basis for ABA hypersensitivity in alix-1 mutants. Our findings unveil a negative feedback mechanism triggered by ABA that acts via ALIX to control the accumulation of specific PYR/PYL/RCAR receptors.